2018
DOI: 10.12775/ths.2018.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of University Students’ English Grammar Proficiency in terms of CEFR Criterial Achievement Levels: the Case of Lithuanian University of Educational Sciences

Abstract: Alignment of language teaching and learning with the CEFR is a complicated process. One of the steps in this process is the analysis and evaluation of student performances characteristic of one or another achievement level (Council of Europe, 2018). The current paper focuses on the exploration of university students' English grammar proficiency in terms of CEFR proficiency levels. However, CEFR levels are underspecified with respect to key properties that are tested and assessed by FL teachers and examiners wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Teachers adopted LPS as an assessment for learning. LPS are benchmarks of assessments to evaluate students’ language proficiency more accurately and pinpoint essential trends in developing students’ language competency (Mazlaveckienė, 2018). They could also be references to diagnostic assessments, from which the feedback could inform students what remedial works should be performed to improve their language proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers adopted LPS as an assessment for learning. LPS are benchmarks of assessments to evaluate students’ language proficiency more accurately and pinpoint essential trends in developing students’ language competency (Mazlaveckienė, 2018). They could also be references to diagnostic assessments, from which the feedback could inform students what remedial works should be performed to improve their language proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Mazlaveckienė (2018) used the CEFR grammar scales to assess Lithuanian English Philology students. Results indicated that these students had a limited repertoire of grammatical structures ranging from level B1 to B2.…”
Section: Synthesis and Findingsmentioning
confidence: 99%